Bizarre Parosteal Osteochondromatous Proliferation (Nora Lesion): A Narrative Review - Edoardo Ipponi; Elisa Ferrari; Alfio Damiano Ruinato; Silvia De Franco; Rodolfo Capanna; Lorenzo Andreani (Acta Medica Lituanica, 2022)
Background: Bizarre parosteal osteochondromatous proliferation (BPOP), or Nora lesion, is a rare proliferative disease arising from the parosteal region of bones. Although BPOP’s pathogenesis is still not certain, modern literature suggests it to be a tumor-like lesion or even a benign neoplasm. Due to the extremely low incidence, to this date studies on the topic are limited to case reports and a few case series. This narrative review aims to resume literature on BPOP and provide an overview of its natural history, morphologic characteristics and prognostic horizon. Materials and methods: A systematic research of the literature was done to identify studies reporting on patients who suffered from BPOP between 1983 and 2021. We collected data regarding aetiologic and pathogenetic theories, patients’ personal data and anamnesis, lesions’ location, clinical presentation, imaging features, pathological appearance, treatment and prognosis. Results: We identified 322 cases of BPOP with a mean age of 34.3 years at the moment of diagnosis. There was no gender difference. The most involved site was the hand, followed by the foot. A history of trauma was reported for 14.7% of the cases. 38.7% of the patients had pain. Literature defined typical radiographic and microscopic patterns that characterize Nora lesions. While imaging is fundamental to orientate towards BPOP, histological evaluation is mandatory to get the definitive diagnosis. To this date, only reliable therapeutic option is represented by surgical resection. BPOP is burdened by a risk of recurrence that accounts to 37.4%. Conclusion: BPOP is a rare benign disease that should be considered during the differential diagnosis of parosteal lesions, especially in the acral regions. Careful diagnostic evaluations are necessary to get the correct diagnosis and wide margins of resection are recommended to minimize the relatively high risk of local recurrence.